Antioxidant and Anti Inflammation Effect of Snack Bars from Black Glutinous Rice and Pumpkin Powder - Mustofa, Akhmad; Suhartatik, Nanik; Ningrum, Ega Sulistiyo (Talenta Publisher, 2019)
The study was design to evaluate the antioxidant and anti-inflammatory effect of snack bars that made of black glutinous rice and pumpkin powder and study on the male Sprague Dawley rats. Twenty-five male rats in between the age of 2 and 3 months were selected and randomly divided into 5 groups, which were positive control, negative control, group with sylimarin treatment, snack bars A and snack bars B. Carbon tetrachloride was used to induce hepatic damage. The results showed that group with CCl4 treatment has 3.04 ± 0.16 μmol/L MDA while group with Sylimarin, snack bars A, snack bars B were 0.49 ± 0.05; 0.54 ± 0.05; and 1.15 ± 0.16 μmol/L MDA, respectively. The snack bars had the capacity to decline the damage in liver as much as Sylimarin (standardized natural medicine for hepatotoxicity). The SGPT (Serum Glutamin Pyruvic Transaminase) of the two treatment was 22.24 ± 0.80 U/I for Sylimarin and 22.33 ± 1.03 U/I for snack bars while SGOT (Serum Glutamic Oxaloacetic Transaminase) was 40.78 ± 0.77 U/I for Sylimarin and 40.88 ± 1.25 U/I for snack bars A. Snack bars B has a significantly different value on final SGOT and SGPT.